Pengembangan Ekonomi Biru Melalui Optimalisasi Pengelolaan Tambak Garam Nunkurus di Kecamatan Kupang Timur, Kabupaten Kupang - Yutriani Andhika; David B.W. Pandie; Maria M. Lino; Syukur Adang Djaha (LPPM Institut Pendidikan Nusantara Global, 2025)
The blue economy concept emphasizes a balance between economic growth, marine environmental conservation, and improving the welfare of coastal communities. Nunkurus Village has great potential to be developed as a model for blue economy-based salt pond management. There are several problems that need to be addressed, such as technological limitations and institutional aspects that are not yet functioning optimally. Research is needed to examine strategies for optimizing salt pond management in Nunkurus Village within the framework of sustainable blue economy development. This research is important because it uses a blue economy approach to optimize salt ponds in Nunkurus Village, Kupang Regency, East Nusa Tenggara. The results of this research indicate that the adoption of technology in Nunkurus Village's salt ponds is still low, weak coastal spatial planning, and a lack of preparedness for climate change cause the ponds to operate inefficiently and be vulnerable to weather disruptions. Salt ponds in Nunkurus Village can only produce 70–80 tons of salt per hectare per year with NaCl content ranging from 90–93 percent, resulting in consistently low selling prices. The optimization strategies that can be implemented are (1) increasing technology adoption and (2) enhancing human resource professionalism and institutional capacity.